Surveying unmet pediatric urological needs in low- and middle-income countries. Issue 2 (April 2021) - Kisa, Phyllis; Scotland, Kymora; Afshar, Kourosh; MacNeily, Andrew E.
Summary: Introduction: Access to pediatric urological surgery is low in low-and-middle income countries (LMICs). Pediatric Urological missions have often been undertaken without best practice guidelines. Many strides have been made in pediatric general surgery and other surgery but little in pediatric urology as a component of global surgery. Study aims: The purpose of this study was to identify challenges to delivery of pediatric urological care in LMICs and make recommendations for its advancement. Study design: An internet search for reports and websites was undertaken. Published surveys from Global Initiative for Children Surgery (GICS) and American Pediatric Surgical Association (APSA) were evaluated. We developed and administered an additional questionnaire. Respondents included LMIC pediatric surgeons, HIC pediatric surgeons and HIC pediatric urologists and LMIC urologists and general surgeons. Results: Most global surgical visits were short one-time visit, and respondents citing complex pediatric urologic patients as most neglected in LMICs with the main challenge reported as a lack of specialist surgeons, poor communication between groups and poor infrastructure. Local specialist training was universally recommended as the most effective way to address unmet needs, although the form of training was not clear. Discussion: Most published work has looked at global general surgery or pediatric general surgery [1] [2] [3] [6] [8] [11] [13] but little on pediatric urology. Most of the information provided was blog posts of social engagements but rarely did these websites provide information on the surgical experience, challenges and solutions gleaned overtime [41] [43][44] [45][56] It is recognised by pediatric urologists, general urologists and pediatric surgeons that complex urologic anomalies are the most neglected among children's surgical conditions with a higher disability weight attributed to urologic conditions compared to anorectal conditions. [6] [8] [14] [27] [31][36] [46], yet there's little expertise on ground and many challenges to its advancement. This study was limited by the number of questions we could explore due to the need to make questions fewer and more concise. Conclusions: Pediatric urological conditions remain among the most neglected in global surgery. Current missions face significant challenges that may result in suboptimal outcomes. A comprehensive effort to establish guidelines for these missions is imperative. Summary Table Survey and responses: Vancouver survey (69 HIC Pediatric urologists and LMIC urologists and general surgeons), APSA survey (131 American pediatric surgeons), GICS survey (41 LMIC children's surgeons) Most neglected conditions: Hypospadias, Bladder/cloacal exstrophy, Neurogenic bladder, Hernias and hydroceles, DSD Challenges: Infrastructure deficiencies, Socio- cultural, Lack of consumables, Inadequate Training, Lack of data repository, Lack of communication between HIC teams